2022
DOI: 10.3390/nu14173638
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential and Pharmaceutical Development of a Multitargeted Flavonoid Phloretin

Abstract: Phloretin is a flavonoid of the dihydrogen chalcone class, present abundantly in apples and strawberries. The beneficial effects of phloretin are mainly associated with its potent antioxidant properties. Phloretin modulates several signaling pathways and molecular mechanisms to exhibit therapeutic benefits against various diseases including cancers, diabetes, liver injury, kidney injury, encephalomyelitis, ulcerative colitis, asthma, arthritis, and cognitive impairment. It ameliorates the complications associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 136 publications
0
15
0
1
Order By: Relevance
“…24 Conventional treatment options do not fulfill all therapeutic needs; hence, most diabetic patients are taking complementary alternative medicines for more benefits. 25,26 Phloretin is one such nutritional supplement that can be taken along with other conventional medicines to fulfill that gap against AKI under diabetic conditions. Considering its multidimensional therapeutic effects (anti-diabetic, anti-inflammatory, anti-cancer, and hepatoprotective), phloretin was also recently studied as a TLR4 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…24 Conventional treatment options do not fulfill all therapeutic needs; hence, most diabetic patients are taking complementary alternative medicines for more benefits. 25,26 Phloretin is one such nutritional supplement that can be taken along with other conventional medicines to fulfill that gap against AKI under diabetic conditions. Considering its multidimensional therapeutic effects (anti-diabetic, anti-inflammatory, anti-cancer, and hepatoprotective), phloretin was also recently studied as a TLR4 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…At last, although PHL has a variety of biological activities, its application as a drug and additive has been restricted due to its low aqueous solubility, poor absorption and bioavailability, and PHL is quickly excreted from the body after absorption [54]. At present, the problem of poor absorption and bioavailability of PHL has been solved by changing its dosage form such as self-nano emulsion [55], liposome [56], and microemulsion formulation [57].…”
Section: Discussionmentioning
confidence: 99%
“…Phloretin is a naturally occurring dihydrochalcone obtained from various vegetables and fruits, mostly found in Manchurian apricots and apple tree leaves . It possesses various therapeutic activities including immunosuppressant, hepatoprotective, antioxidant, cardioprotective, and antidiabetic properties . The study showed that phloretin reduces sunburn which occurs due to UV radiation by suppressing the expression of matrix metalloproteinase-9 and inhibiting thymidine dimer formation.…”
Section: Therapeutic Strategies For the Treatment Of Skin Cancermentioning
confidence: 99%